(untitled) (Al-Academy, 2018)
The printing designer’s creative thinking is a deliberate mental process based on specific skills that stimulate the motivation of the student to learn and call for new information for the investigation and research to discover the problems and attitudes and through reformulating the experience in new patterns depending on the active imagination and the flexible scientific thinking through providing the largest number possible of various unfamiliar printing design models, and testing their suitability and then readjusting the results with the availability of suitable educational, learning and academic atmosphere. The designer’s creative thinking depends on main skills. Fluency skill is to put the largest number of the given designs and ideas. Flexibility skill is the diversity of these ideas. The originality skill is the production of ideas and designs characterized by excellence. Problem sensitivity skill is represented by (analysis and synthesis). The detailing skill is represented by the largest number of details and finally the assessment skill is represented by (examination, assessment, and determining the final design). The objectives of the research are as follows: Designing an educational model in the journalistic direction course. Measuring the effectiveness of the educational model in developing the creative thinking through its application to an experimental sample of printing design students. The researcher, thus, intentionally chose the study community from the students of the department of printing design/ the Institute of Fine Arts- the evening study for the academic year (2017-2018) which was made of (20) students taken all for the sample and divided into two (experimental and controlling ) groups , ten students in each group.